Peran Notaris dalam Legalitas Dokumen dan Kontrak Internasional: Studi Perbandingan antara Negara Indonesia dan Malaysia - Alda Widya Syahda; Suhaidi; Jelly Leviza (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Differences between civil law and common law systems affect the position, authority and role of notaries in the legality of international documents and contracts. Indonesia, as a country adhering to the civil law system, grants broad authority to notaries to prepare authentic deeds, perform legalization, waarmerking and certify documents. Furthermore, Indonesia became a Contracting Party to the Hague Apostille Convention on 5 October 2021 and the Convention entered into force on 4 June 2022, enabling Indonesian public documents to be authenticated through the Apostille mechanism for use in other Contracting States. In contrast, Malaysia, which follows the common law system, is not a Contracting Party to the Hague Apostille Convention as of 2026. Consequently, Malaysian public documents intended for use abroad remain subject to the conventional legalization process through the competent authorities. This normative legal research employs statutory, conceptual and comparative approaches. The results show that Indonesian notaries perform broader functions than Malaysian Notaries Public, whose authority is generally limited to the authentication and legalization of documents. Accordingly, Indonesian notaries play a more strategic role in ensuring legal certainty, formal validity and the evidentiary value of international documents and contracts.